PENGARUH KUALITAS AUDIT DAN PENGALAMAN AUDITOR TERHADAP KEMAMPUAN PENILAIAN KECURANGAN AUDITOR - Muhamad Abdul Hafizh; Yuha Nadhirah Qintharah (Komunitas Dosen Indonesia, 2024)
Several companies use various methods to commit fraud in financial reporting in order to get a good performance assessment. The case of alleged manipulation of financial reports that has occurred is the case of PT Envy Technologies Indonesia Tbk. The issuer is suspected of committing fraud after 2 years of being registered as a public company on the IDX since July 9 2019. This study aims to determine the effect of audit quality and auditor experience in detecting fraud that occurs (fraud). The study employs quantitative methods with the assistance of SPSS IBM 20. The population consists of auditors working at Public Accounting Firms in the Jakarta and Bekasi regions, selected using a purposive sampling method based on specific criteria. Data collected by using questionnaire sharing by google form and immediately sharing. Based on the highest variable indicators, a total of 145 auditors were selected as respondents. The study's findings indicate that the audit quality variable has a significantly positive impact on the ability to detect fraud. This is attributed to the fact that higher auditor competence leads to faster and more accurate fraud detection. Additionally, the auditor's experience variable also positively and significantly influences the ability to detect fraud, suggesting that the longer an auditor's work experience with diverse levels of workload complexity, the better their capability to identify fraud in financial statements.